BERTEOLOGI KONTEKSTUAL DARI PERSPEKTIF ORANG KEI MELALUI KONSEP DUAD - MARTHINUS NGABALIN (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
The encounter between the official religion and local values also gives specificity to theology. It can be traced to the use of Duang and Duad terms, which the Kei people understand as God. Kei people know that God is present in everyday life, but His name is also very sacred, so it can not be called arbitrarily. Though they have embraced Christianity, they still believe in Duad in their cultural and diverse peculiarities. The method used is qualitative research with a contextual theological concept. The finding of this research is the Kei who have embraced Christianity remain confident in the Duad in their daily lives.